(untitled) (Revista Espinhaço, 2023)
Family farming has an important role for rural development, being one of the pillars of the Brazilian agricultural sector, which reveals the importance of public policies specifically designed for this sector, such as Pronaf. This study aims to understand the effects of the National Family Farming Program (Pronaf), as a rural credit policy, on the lives of farmers in the semi-arid north of Minas Gerais (Brazil), in the municipality of Porteirinha. The objective is to analyze the perception of female farmers about the changes that occurred in their socioeconomic situation, as well as in inequality in gender relations, due to having been awarded with credits from Pronaf. The study was based on semi-structured interviews with 12 farmers who accessed Pronaf between 2005 and 2018, residing in Porteirinha. We find that the farmers’ autonomy is restricted only to the administration of female income itself, and that the transformations provided were not significant in the family sphere, management and participation in the property. However, there have been positive changes in the reality and in the lives of women, although the path to overcome inequalities in gender relations and socioeconomic inclusion still seems long.